Importation of Ideologies from Macaulay Minutes to Wood Commission - Awasthi, Lava Deo (Journal of Education and Research, 2008)
In this article I examine Nepal’s language policy with particular reference to Nepal National Education Planning Commission (NNEPC known as Wood Commission) Report of 1956. In this essay I analyze how the Wood Commission Report was employed as a means of importing values introduced by the British India’s Macaulay Minutes of 1835. I explore how the post independence Education Commission had an overarching effect on the educational language policy discourse in the country. I investigate the effects of the NNEPC language policy on the educational practices in Nepal. First, I consider how the independent Nepal responded to the aspirations of the people for change in its educational language planning and policy. DOI: http://dx.doi.org/10.3126/jer.v1i0.7948 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 21-30